1992
DOI: 10.1007/bf02245139
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economics of drug self-administration

Abstract: In behavioral economics, consumption of a reinforcer is determined by its price and by the price of other available reinforcers. This study examined the effects of price manipulations on the consumption of concurrently available coffee and cigarettes. During fifteen 4-h sessions, coffee and cigarettes were concurrently available according to fixed-ratio (FR) schedules of reinforcement. After consumption stabilized under a fixed ratio 100 for both reinforcers, the response requirement for each reinforcer was va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The earliest procedures were based on those use in animal self-administration studies and extended to the human laboratory. 5 These self-administration studies required many sessions with long durations and could only conveniently compare consumption of a few products. The next step in this evolution entailed a questionnaire measuring self-reported consumption of cigarettes at prices ranging from free to $100.00 per cigarette referred to as the hypothetical purchase task.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…The earliest procedures were based on those use in animal self-administration studies and extended to the human laboratory. 5 These self-administration studies required many sessions with long durations and could only conveniently compare consumption of a few products. The next step in this evolution entailed a questionnaire measuring self-reported consumption of cigarettes at prices ranging from free to $100.00 per cigarette referred to as the hypothetical purchase task.…”
Section: Discussionmentioning
confidence: 41%
“…For example, the consumption of coffee has been shown to decrease with increasing cigarette prices, even though the price of coffee remained constant. 5 Between these two extremes is independence, which occurs when changes in the price of one commodity have little or no effect on consumption of another constantly priced commodity. For example, in a study where smokers completed response requirements to obtain concurrently available money and cigarette puffs, independence between commodities was found; that is, as cigarette consumption decreased with increasing price, the amount of money earned remained stable.…”
Section: Original Investigationmentioning
confidence: 39%
“…Previous research has shown that consumption of coffee decreases as the unit price of cigarettes increases (i.e., caffeine is a complement to cigarettes (Bickel et al, 1992)). Likewise, increasing cigarette taxes decreases alcohol and marijuana consumption (Lee, 2007, Dee, 1999, Chaloupka et al, 1999, Pacula, 1998, Farrelly et al, 2001), suggesting that consumption of alcohol and marijuana may decrease following nicotine reduction.…”
Section: How Is a Nicotine Reduction Policy Related To The Consumpmentioning
confidence: 99%
“…Some human laboratory studies have utilized a task in which smokers make an effortful response to receive access to either cigarettes or another product (Bickel et al, 1992, Bickel and Madden, 1999, Johnson and Bickel, 2003, Johnson et al, 2004). The unit price of cigarettes can be raised in the presence of other products, so that the interactions between the unit prices of products can be considered.…”
Section: How Is a Nicotine Reduction Policy Related To The Consumpmentioning
confidence: 99%
“…In a separate study, young adult smokers in a cessation program who had an increase in substitute reinforcers during the treatment period were nearly twice as likely to quit smoking at the end of treatment (Audrain-McGovern et al, 2009). While studies of adolescents, human laboratory studies (Epstein et al, 1991; Bickel et al, 1992, 1995; MacKillop et al, 2012; Acker and MacKillop, 2013), and studies using financial incentives to promote smoking abstinence (e.g., Volpp et al, 2009) have demonstrated the influence of alternative reinforcers on smoking behavior, to our knowledge, the relationship between self-reported, naturally occurring alternative reinforcers (vs. study-related financial incentives) and smoking cessation has yet to be studied within a clinical trial of adult treatment-seeking smokers.…”
Section: Introductionmentioning
confidence: 99%